2020
DOI: 10.34306/ajri.v2i1.55
|View full text |Cite
|
Sign up to set email alerts
|

Total Quality Management Through Lecturer Assessment With Students to Improve Graduate Quality

Abstract: Total Management System or abbreviated as TQM is a management system quality that is focused on the customer (Customer focused) by involving all levels of employees in making improvements or continuous improvements (in a manner continuously). Total Quality Management or TQM uses strategy, data and effective communication to integrate quality discipline into culture and company activities. In short, Total Quality Management (TQM) is a management approach to achieve long-term success through satisfaction Custome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This means that the better the quality of Chatime's products and the right advantages, the Chatime customers will be satisf ied with what they get; (3) promotion af f ects cust omer satisf action Chatime. With the more attractive promotions the company applies to consumers, Chatime provides many discounts and promotions on social media, the more satisf ying customers will be; (4) service quality, product quality, and promotions tog ether af f ect Chatime's customer satisf action; (5) shows that the dominant inf luence on Chatime customer satisf action is promotion. It was concluded that the hypothesis which stated that service quality (X2) had the most dominant ef f ect, was not proven.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the better the quality of Chatime's products and the right advantages, the Chatime customers will be satisf ied with what they get; (3) promotion af f ects cust omer satisf action Chatime. With the more attractive promotions the company applies to consumers, Chatime provides many discounts and promotions on social media, the more satisf ying customers will be; (4) service quality, product quality, and promotions tog ether af f ect Chatime's customer satisf action; (5) shows that the dominant inf luence on Chatime customer satisf action is promotion. It was concluded that the hypothesis which stated that service quality (X2) had the most dominant ef f ect, was not proven.…”
Section: Discussionmentioning
confidence: 99%
“…The Edublocs project, allowing students to create their own study schedules, has encouraged students to realize the potential contribution that the application of LO can make to their learning. With regard to the use of Blockchain in projects, it is possible to pay attention to its potential, not only for the implementation of this particular initiative, but also for personalized learning itineraries in a global environment [47]. With students, teacher-tutors, and LO trainers from various organizations and countries, Blockchain offers a systems system that guarantees the various actors that make up the learning process, as well as the skills that are assimilated.…”
Section: Discussionmentioning
confidence: 99%
“…Technological developments have resulted in the emergence of a new technology called blockchain, this technology has advantages in terms of security, because it is a recorder that records open transactions and uses a decentralized database without going through third party intermediaries [17]. Initially blockchain was only used for transactions from encrypted electronic currencies such as bitcoin, but along with more in-depth research on developing currencies, blockchain technology is increasingly developing, not only for making transactions, but this technology is also related to existing technology [18]. like topology.…”
Section: Blockchainmentioning
confidence: 99%